CLINICAL AND EEG PREDICTORS OF INCREASED FREQUENCY OF GENERALIZED SEIZURES IN GESTATIONAL AND POSTGRAVIDARUM PERIOD - O. V. Grebenyuk; M. V. Svetlik; V. M. Alifiriva; I. D. Yevtushenko; Yu. A. Bochkov; I. A. Stepanov (Бюллетень сибирской медицины)
We investigated the predictors of increased seizures’ frequency among women with various forms of idiopathic generalized epilepsies (IGE) in the gestational and postgravid period. We observed 41 patients with Idiopathic generalized epilepsy (IGE) before, during and after pregnancy. During the period of observation EEG was recorded in the states of relaxed and active awakeness and sleeping. Patients, who have stopped to take anticonvulsants before pregnancy, have had increased frequency of seizures, more than1 ina year, with interictal epileptiform discharges in a state of relaxed and active awakeness. Increased seizures after pregnancy was observed in patients with interictal epileptiform discharges during sleep. The results can be used during the preparation of pregravid women with IGE.